2001
DOI: 10.1016/s0272-6963(00)00066-8
|View full text |Cite
|
Sign up to set email alerts
|

JIT purchasing and performance: an exploratory analysis of buyer and supplier perspectives

Abstract: In this exploratory analysis, a model is developed and tested to determine whether the use of JIT purchasing reduces logistics costs for both suppliers and buyers. The results indicate that JIT purchasing directly reduces costs only for buyers. An indirect path, however, was found between JIT purchasing and logistics costs for suppliers. To the extent that JIT purchasing may result in suppliers adopting JIT manufacturing techniques, then suppliers too can benefit, at least indirectly, from JIT purchasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(98 citation statements)
references
References 40 publications
5
84
0
1
Order By: Relevance
“…As buyers work toward just-in-time delivery and seek to reduce their risk of over-or under-buying (Dong et al, 2001), they often deliberately defer a decision until the last possible minute in order to understand better what their competitors might do and to reflect exactly current consumer demands, either in terms of volume or product specification (Ashida and Plinke, 2004). To fill these short-lead time and highflexibility orders, suppliers in developing countries may either force extreme overtimes or speed up production lines to extreme physical limits (The Impactt Overtime Project Report, 2005).…”
Section: Production Complexitymentioning
confidence: 99%
“…As buyers work toward just-in-time delivery and seek to reduce their risk of over-or under-buying (Dong et al, 2001), they often deliberately defer a decision until the last possible minute in order to understand better what their competitors might do and to reflect exactly current consumer demands, either in terms of volume or product specification (Ashida and Plinke, 2004). To fill these short-lead time and highflexibility orders, suppliers in developing countries may either force extreme overtimes or speed up production lines to extreme physical limits (The Impactt Overtime Project Report, 2005).…”
Section: Production Complexitymentioning
confidence: 99%
“…Complementarily, O'Leary-Kelly and Flores (2002) argued that manufacturing and marketing integration improves business performance. Similarly, other studies indicate that integration among functional areas influences operational or business performance (Droge, Jayaram, & Vickery, 2004;Swink, Narasimhan, & Wang, 2007): among others, manufacturing and supply chain integration (Flynn et al, 2010;Narasimhan & Kim, 2002), supply chain and NDP integration (Primo & Amundson, 2002), and buyer and supplier integration (Dong, Carter, & Dresner, 2001). At the same time, integration is a result of different activities.…”
Section: Results Expectedmentioning
confidence: 87%
“…We evaluated how often manufacturing seeks to improve coordination with external and internal actors (Dong et al, 2001;Frohlich & Westbrook, 2002;Koufteros et al, 2005;Monczka et al, 1998;Vickery, Jayaram, Droge, & Calantone, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Examples include the use of EDI, decisions regarding packaging, or synchronisation of deliveries. Authors that stand out for conceiving integration as practices include: Dong et al (2001), Salvador et al (2001), Frohlich and Westbrook (2001), Vickery et al (2003), Kulp et al (2004); Narasimhan and Nair (2005) or Sanders and Premus (2005). Van der Vaart and Van Donk (2008) concluded that there is an excessive amount of variation in the ways different authors capture the concept of integration and, although there are authors who have combined two of the dimensions and even the three dimensions, they are still concerned with the influence that attitudes, patterns and practices have on each other.…”
Section: Integration Contentmentioning
confidence: 99%